Hubungan Indeks Risiko Sanitasi dengan Kejadian Stunting di Kelurahan Pesawahan Kota Bandar Lampung - Rega Wahyudi; Khoidar Amirus; Vera Yulyani (Malahayati Nursing Journal, 2024)
ABSTRACT  Stunting is a condition where toddlers have a long body or height that is less when compared to age. The prevalence of stunting in the city of Bandar Lampung is (36.1%), data at UPT Pasar Ambon Health Center, Bandar Lampung city, the prevalence of stunting in the Pesawahan sub-district is 44 (2, 14%). This study aims to determine the relationship between the risk of the sanitation index and the incidence of stunting in the rice fields of Bandar Lampung City in 2022. This type of research uses a quantitative study with a cross-sectional design using a total of 92 respondents. The sampling technique used was purposive sampling technique. univariate and bivariate analysis test with chi square test. The results of the stunting detection analysis detected 28 (30.4%) respondents. Sanitation risk index. Water source risk was 23 (36.5%) respondents. Domestic wastewater sanitation risk index was 5 (71.4%) respondents. The risk sanitation index for clean and healthy behavior is at risk of 3 (75.0%) respondents. The results of the bivariate analysis showed that there were 2 variables related to stunting, namely the domestic waste sanitation risk index (p value 0.014 Odds Ratio 6.739), sanitation risk index clean and healthy living behavior (p value 0.048 Odds Ratio 7.560). The variable that is not related to stunting is the air source sanitation risk index (p value 0.062). Research suggestions based on research results show that there is a relationship between the sanitation index of risk of domestic wastewater and the sanitation index of clean and healthy living behavior with the incidence of stunting, it is necessary to improve awareness of reduced domestic wastewater treatment and the importance of awareness of clean and healthy living behavior. Keywords: Stunting, Sanitation, IRS  ABSTRAK Stunting merupakan kondisi dimana balita memiliki panjang atau tinggi badan  yang kurang jika dibandingkan dengan umur, Prevalensi kejadian stunting dikota Bandar Lampung sebesar (36,1%), data di UPT Puskesmas Pasar Ambon kota Bandar Lampung prevalensi stunting di kelurahan Pesawahan sebanyak 44 (2,14%).  Penelitian ini bertujuan mengetahui hubungan indeks risiko sanitasi dengan kejadian stunting di kelurahan pesawahan kota bandar lampung tahun 2022. Jenis penelitian ini menggunakan penelitian kuantitatif dengan rancangan cross sectional menggunaan sebanyak 92 responden. Tenik sampling yang digunakan dengan Teknik purposive sampling. uji analisis univariat dan bivariat dengan uji chi square. Hasil analisis menunjukan terdeteksi stunting sebanyak 28 (30,4%) responden, Indeks risiko sanitasi Sumber air berisiko sebanyak 23 (36,5%) responden, Indeks risiko sanitasi air limbah domestik berisiko 5 (71,4 %) responden. Indeks risiko sanitasi perilaku hidup bersih dan sehat berisiko sebanyak 3 (75,0%) responden. Hasil analasis bivariat menunjukan bahwa terdapat 2 variabel yang berhubungan dengan stunting, yaitu indeks risiko sanitasi limbah domestik (p value 0,014 Odds Ratio 6,739), indeks risiko sanitasi prilaku hidup bersih dan sehat (p value 0,048 Odds Ratio sebesar 7,560). Variabel yang tidak berhubungan dengan stunting adalah indeks risiko sanitasi sumber air (p value 0,062). Saran penelitian berdasarkan hasil penelitian didapatkan hubungan indeks risiko sanitasi air limbah domestik dan indeks risiko sanitasi prilaku hidup bersih dan sehat dengan kejadian stunting maka perlunya dilakukan perbaikan kesadaran akan pentingnya pengolahan air limbah domestik dan pentingnya kesadaran  prilaku hidup bersih dan sehat.  Kata Kunci: Stunting, Sanitasi, IRS